HUBUNGAN PENGETAHUAN GIZI, STATUS GIZI, ASUPAN KALSIUM, MAGNESIUM, VITAMIN B6 DAN AKTIVITAS FISIK DENGAN SINDROM PRAMENSTRUASI (STUDI PADA MAHASISWI PEMINATAN GIZI KESMAS FKM UNDIP TAHUN 2017) - Anggraeni, Nurul; Pangestuti, Dina Rahayuning; Aruben, Ronny (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Premenstrual syndrome (PMS) is a collection of physical, psychological and emotional symptoms associated with a woman's menstrual cycle. Calcium and magnesium affect the hormone estrogen. Vitamin B6 has an important role in the formation of serotonin associated with premenstrual syndrome.The aim of this study to analyze the relationship of nutritional knowledge, nutritional status, calcium, magnesium, vitamin B6 intake and physical activity with premenstrual syndrome. This research is a quantitative research with cross sectional approach. Samples were taken using total sampling technique with 40 respondents. Data were obtained by interview using nutrition knowledge questionnaire, Shortened Premenstrual Assessment Form (sPAF), 2x24 hour physical activity recall sheet and Semi Quantitative FFQ sheet. Data were analyzed by univariate and bivariate using Rank Spearman and Pearson Product Moment test. The results showed that 70% of respondents had enough knowledge category, 57.5% of respondents had normal body mass index (BMI), 50% of respondents had mild activity level, 55% had premenstrual syndrome with moderate to severe symptoms, 62.5% of respondents had less calcium adequacy, while the magnesium adequacy (70%) and vitamin B6 (67.5%) were adequate. The results showed there was no correlation between nutritional knowledge with calcium, magnesium and vitamin B6 intake (p>0.05). There was a relationship between nutritional status and premenstrual syndrome (p <0.05) and no association between calcium intake, magnesium, vitamin B6 and physical activity with premenstrual syndrome (p>0.05).